Literature Review: The Role Of Employee Development In Improving Employee Performance - Novriyanti Zebua, Tety; Humaira, Siti; Miranda Nst, Meirizka; F. Dalimunthe , Ritha (Jurnal Syntax Fusion, 2024)
To face the demands of the task and especially to answer the challenges of the future, employee development is an absolute must. With a good employee development program, the organization will have a more effective competitive strength and be able to compete positively in the global arena and be difficult to imitate by other organizations. This study aims to determine how employee development improves employee performance in an organization/company. This study uses an in-depth literature review method, where various sources of literature relevant to the research topic are collected and analyzed carefully. The results of the literature review show that Employee Development has a positive impact on improving employee performance. It can be concluded that employee development is relevant to be implemented by organizations or companies in order to improve employee skills, capabilities and productivity. The implications of this study include the importance of training and development programs with individual needs and company strategies.